POLY FRACTION (TRIMETILEN-BASED) FROM MONOMER RENEWABLE ONLY SOLUTION AND DECREASE TEMPERATURE - Diah Mardiana; Bambang Poerwadi; Budi Kamulyan; Siannita Chandra (Jurnal Penelitian Saintek, 2014)
Poly(trimethylene-sebacate), polyester material from glycerol and castor oil monomer resources, have been synthesized. Fractionation using suitable solvent-non solvent composition could be produced the pure polymer. In this experiment dissolution methods were modified by reduced temperature. In order to choose the suitable solvent and its composition, it was monitored by the turbidity, while the effect of reduced temperature were analysed based on poly(trimethylene-sebacate) mass and several physical properties of product. Result showed that the suitable solvent and non solvent were chloroform and methanol, respectively. As with out reduced temperature, the volume composition was 1 : 10, while temperature modified could be reduced 50% of methanol used. Furthermore, concentration of poly(trimethylene-sebacate) of 3% using volume composition of 1 : 5 at temperature of 20-22 oC , it was yielded 48.4% of product. It has melting point of 52 C with intrinsic viscosity of 10.89 mL/g, Mn 2632 g/eq and degree of crystalinity was 30.5%.